Analisis Yuridis Tindak Pidana Penipuan Atas Tipu Muslihat Terhadap Pekerja Seks Komersial Berdasarkan Pasala 378 Kuhp Tentang Tindak Pidana Penipuan - Rania Chaerunnisa; Aryo Fadlian (Peneliti.net, 2022)
This crime, regulated under Article 378 of the Criminal Code, is primarily known as fraud and is commonly referred to as “opriching.” Article 378 of the Criminal Code states: